1998
DOI: 10.1104/pp.118.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Callose Deposition Is Responsible for Apoplastic Semipermeability of the Endosperm Envelope of Muskmelon Seeds1

Abstract: Semipermeable cell walls or apoplastic "membranes" have been hypothesized to be present in various plant tissues. Although often associated with suberized or lignified walls, the wall component that confers osmotic semipermeability is not known. In muskmelon (Cucumis melo L.) seeds, a thin, membranous endosperm completely encloses the embryo, creating a semipermeable apoplastic envelope. When dead muskmelon seeds are allowed to imbibe, solutes leaking from the embryo are retained within the envelope, resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 33 publications
(21 reference statements)
1
78
3
Order By: Relevance
“…5B). It has been reported that callose deposition, which was detected by aniline blue and is induced by wounding stress or pathogen infection, was detected among the fungal infection patterns (Yim et al, 1998). The invading hyphae with serious branch spread were detected in infected leaves at 48 h with DMSO or PI treatment (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…5B). It has been reported that callose deposition, which was detected by aniline blue and is induced by wounding stress or pathogen infection, was detected among the fungal infection patterns (Yim et al, 1998). The invading hyphae with serious branch spread were detected in infected leaves at 48 h with DMSO or PI treatment (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…In this context, the accumulation of callose in the chalazal cell wall (Figure 3) is puzzling, because this Glc polymer has been shown to restrain apoplast transport in seeds (Yim and Bradford, 1998). One possible explanation is that callose may function as a selective barrier to the transport of molecules into the endosperm from the surrounding maternal tissues.…”
Section: Why Does the Chalazal Endosperm Domain Transiently Store Mn mentioning
confidence: 93%
“…Callose deposition at the ovule chalazal end has been traditionally used as a microscopic feature to assess early ovule degeneration (Vishnyakova, 1991). Callose deposits play different functions in plant development and, although the function of callose has been interpreted traditionally to isolate dying from living cells, callose might also inhibit sugar transport to the aborting embryo sac (Sun et al, 2004) inasmuch as it limited the diffusion of small sugar molecules to the developing muskmelon (Cucumis melo L.) embryo (Yim and Bradford, 1998). Whether this is a cause or a consequence of female gametophyte degeneration is not known.…”
Section: Female Development: the Pistil And The Female Gametophytementioning
confidence: 99%